The new linguistics of speech - Helberg Chávez, Heinrich (2017)
The present article aims to formulate the fundamentals of a new linguistics that is focused on the daily experience of speech and denies the existence of codes as an explaining devise of language understanding and gives them only a symbolic value. Instead the new linguistics develops an interactive hermeneutic to understand the mechanisms of speech, the acquisition of language and its practical logic that constitutes the universe of meaning, because we speak as we learned to do it. The new linguistics is focused in the interests of the speaker who wants to own his own way of speaking and define the meanings in concrete situations, in contrast with a linguistics that defends the collective national interests symbolized in the shared codes.